2014
DOI: 10.1097/ta.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Blunt Abdominal Trauma in Children (BATiC) score

Abstract: Prognostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…In this group, 8/11 (73%) of the FAST scans, 1/11 (9%) of the complete abdominal ultrasound scans and 1/13 (8%) of the CT scans had negative results. Injuries were located in the spleen (5), liver (5), kidneys (3) and bladder (1). In 50% of the cases, the abdomen AIS was greater than or equal to three.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In this group, 8/11 (73%) of the FAST scans, 1/11 (9%) of the complete abdominal ultrasound scans and 1/13 (8%) of the CT scans had negative results. Injuries were located in the spleen (5), liver (5), kidneys (3) and bladder (1). In 50% of the cases, the abdomen AIS was greater than or equal to three.…”
Section: Resultsmentioning
confidence: 98%
“…In 2014, De Jong et al [1] reported good results obtained with the BATiC score, used in children, which can rule out the presence of intra-abdominal injuries in approximately 50% of cases. Also in 2014, Shojaee et al [27] reported good results with the BATSS score as well, which could limit the use of abdominal CT scans in a large number of blunt trauma victims.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…7 This protocol was further validated in a subsequent study. 8 A large prospective trial that used only history and physical examination findings identified patients at very low risk for intraabdominal injury, and therefore would not need an abdominal CT. 9 While ultrasound and clinical examination are not quite as sensitive as CT using these algorithms, or other similar protocols, may help guide selective and efficient use of CT in suspected abdominal trauma.…”
Section: Diagnosismentioning
confidence: 99%